Diffuse myocardial fibrosis in patients with mitral valve prolapse and ventricular arrhythmia. Issue 3 (11th August 2016) - Bui, An H; Roujol, Sébastien; Foppa, Murilo; Kissinger, Kraig V; Goddu, Beth; Hauser, Thomas H; Zimetbaum, Peter J; Ngo, Long H; Manning, Warren J; Nezafat, Reza; Delling, Francesca N
Abstract : Objective: We aimed to investigate the association of diffuse myocardial fibrosis by cardiac magnetic resonance (CMR) T1 with complex ventricular arrhythmia (ComVA) in mitral valve prolapse (MVP). Methods: A retrospective analysis was performed on 41 consecutive patients with MVP referred for CMR between 2006 and 2011, and 31 healthy controls. Arrhythmia analysis was available in 23 patients with MVP with Holter/event monitors. Left ventricular (LV) septal T1 times were derived from Look-Locker sequences after administration of 0.2 mmol/kg gadopentetate dimeglumine. Late gadolinium enhancement (LGE) CMR images were available for all subjects. Results: Patients with MVP had significantly shorter postcontrast T1 times when compared with controls (334±52 vs 363±58 ms; p=0.03) despite similar LV ejection fraction (LVEF) (63±7 vs 60±6%, p=0.10). In a multivariable analysis, LV end-diastolic volume, LVEF and mitral regurgitation fraction were all correlates of T1 times, with LVEF and LV end-diastolic volume being the strongest (p=0.005, p=0.008 and p=0.045, respectively; model adjusted R 2 =0.30). Patients with MVP with ComVA had significantly shorter postcontrast T1 times when compared with patients with MVP without ComVA (324 (296, 348) vs 354 (327, 376) ms; p=0.03) and only 5/14 (36%) had evidence of papillary muscle LGE. Conclusions: MVP may be associated with diffuse LV myocardial fibrosis as suggested by reduced postcontrast T1 times. Diffuse interstitial derangement is linked to subclinical systolic dysfunction, and may contribute to ComVA in MVP-related mitral regurgitation, even in the absence of focal fibrosis.